Analisis Putusan Nomor 18.Pid.B/2022/PN_Gst Tentang Tindak Pidana Penganiayaan Yang Menyebabkan Luka Berat : Analysis Of Decision Number 18.Pid.B/2022/PN_Gst Concerning The Criminal Act Of Torture Which Causes Serious Injury - Febriolla fransiska sepuwarini; Eriyantouw Wahid (Reformasi Hukum Trisakti, 2024)
The offence of significant injury is a violation of human life, constituting an act that contravenes the law, as exemplified by the case of severe abuse in decision Number 18.Pid.B/2022/PN_Gst in this instance, the assailant perpertrated sever abuse on the victim by inflicting a stab wound to the victim’s abdomen using a knife, which has the potential to be fatal. The author’s problem is to determine if acts of abuse resulting in severe injuries can be classifiend as attrempted murder according to Article 338 in conjunction with Article 53 paragraph 1 of the Criminal Code?. This study uses descriptive analysis, a normative research method. Using literature findings are as follows: (1) The defendant’s conduct do not satisfy the requirements outlined in article 338, in connection with article 53, of the criminal code. (2) Criminal penalties are not imposed in case decision number 18.Pid.B/2021/PN_Gst employs a punishment theory that encompasses four primary objectives: detterent effect, education, rehabilitation, and social control. For this situation, the appropriate legal provision to addres the criminal act of causing severe bodily harm is Article 351, paragraph 2 of the criminal code.